Validation of an updated Associative Transcriptomics platform for the polyploid crop species Brassica napus by dissection of the genetic architecture of erucic acid and tocopherol isoform variation in seeds - Havlickova, Lenka; He, Zhesi; Wang, Lihong; Langer, Swen; Harper, Andrea L.; Kaur, Harjeevan; Broadley, Martin R.; Gegas, Vasilis; Bancroft, I. (Wiley, 2018)
An updated platform was developed to underpin association genetics studies in the polyploid crop species Brassica napus (oilseed rape). Based on 1.92 × 1012 bases of leaf mRNAseq data, functional genotypes, comprising 355 536 single-nucleotide polymorphism markers and transcript abundance were scored across a genetic diversity panel of 383 accessions using a transcriptome reference comprising 116 098 ordered coding DNA sequence (CDS) gene models. The use of the platform for Associative Transcriptomics was first tested by analysing the genetic architecture of variation in seed erucic acid content, as high-erucic rapeseed oil is highly valued for a variety of applications in industry. Known loci were identified, along with a previously undetected minor-effect locus. The platform was then used to analyse variation for the relative proportions of tocopherol (vitamin E) forms in seeds, and the validity of the most significant markers was assessed using a take-one-out approach. Furthermore, the analysis implicated expression variation of the gene Bo2g050970.1, an orthologue of VTE4 (which encodes a γ-tocopherol methyl transferase converting γ-tocopherol into α-tocopherol) associated with the observed trait variation. The establishment of the first full-scale Associative Transcriptomics platform for B. napus enables rapid progress to be made towards an understanding of the genetic architecture of trait variation in this important species, and provides an exemplar for other crops.